Continuous mush disaggregation during the long-lasting Laki fissure eruption, Iceland - Neave, DA; Buisman, I; Maclennan, JC (Mineralogical Society of America, 2017)
Plagioclase textures were investigated in the products of the voluminous AD 1783–1784 Laki eruption from the Eastern Volcanic Zone (EVZ) of Iceland to establish whether mush disaggregation occurred solely at the onset of the eight-month eruption or throughout its whole duration. Phase proportions and plagioclase size distributions were determined using standard optical and manual techniques as well as automated approaches based on Quantitative Evaluation of Minerals by SCANing electron microscopy (QEMSCAN). Based on optical microscopy and the explicit combination of textural and compositional information in QEMSCAN images, plagioclase crystals were divided into two populations: small (<0.5 mm long), high-aspect ratio (length/width > 4) microcrysts with low-anorthite ( 0.5 mm long), low-aspect ratio(length/width = 2–3) macrocrysts with high-anorthite (An₈₄–An₉₂) cores. Small microcrysts grew from their carrier liquid during the final phase of pre-eruptive crystallization while large macrocrysts, which are out of geochemical equilibrium with their carrier liquids, were entrained from crystal mushes. Changes in phase proportions and plagioclase size distributions between eruptive episodes demonstrate that macrocryst entrainment efficiency varied substantially during the eruption; material erupted in later episodes contain proportionally more mush-derived material. Using stereologically corrected plagioclase size distributions, we estimate that the pre-eruptive residence times of microcrysts in the Laki carrier liquid were probably of the order of 2–20 days. Because microcryst crystallization was concurrent with macrocryst rim growth, these day-to-week residence times also indicate that macrocryst entrainment occurred on much shorter timescales than the eruption’s eight- month duration. In line with constraints from independent geochronometers, macrocryst entrainment and mush disaggregation thus appears to have continued throughout the eruption. Magmas were assembled on an episode by episode basis, and the ...